OPTIMALISASI PERAN BUMDES DALAM MENINGKATKAN KEMANDIRIAN DESA (STUDI PADA BUMDES IJEN LESTARI, DESA TAMANSARI, KECAMATAN LICIN KABUPATEN BANYUWANGI) - Permatasari, Safrieta Jatu; Imaniar, Dimas (Universitas Tanjungpura, 2022)
Villages are the spearhead of Indonesia's development. Therefore, the government continues to strive to encourage the village economy by channeling Village Funds and the Village Owned Enterprises (BUMdes) development program. The objectives of BUMDes as stated in Permendesa PDT and Transmigration No. 4/2015 is, improving the village economy, increasing community efforts in managing the village's economic potential. In addition, it also develops business cooperation plans between villages and/or with third parties, creates opportunities and market networks that support the needs of public services for residents, creates employment opportunities, improves community welfare through improving public services, growth and equity in the village economy, and increasing income. village community and village original income. This study analyzes the optimization of the role of Bumdes in increasing village independence. This type of research is descriptive qualitative which aims to determine the optimization of the existence of BUMDes towards increasing community and village independence. The variables used in this study were BUMDes, community empowerment, and increasing village independence. The sampling method used in this research is the snowball method. The results showed that the optimization of the role of Bumdes in increasing village independence in Tamasari Village, Licin District, Banyuwangi Regency could be realized, where since its establishment in 2015, during its development period many programs were developed, which in turn had a positive impact on opening up jobs, increasing the economy. community, as well as increase the income of the Village APBDes.